ASPEK EKOLOGI IKAN KANCERA (TOR SORO) KUNINGAN DAN PEMATANGAN GONAD MELALUI IMPLANTASI HORMON GONADOTROPIN (HCG) - Subagja, Jojo; Sulhi, M.; Asih, Sidi; Haryono, Haryono (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTEcological Aspect and Gonadal Maturation of Tor soro by HCG peletted Implantation. Theexperiment was conducted to determine optimal dosage of Gnrh-a hormon at gonadal maturationof mahseer from Kuningan (Tor soro). The fish was reared in concrete tanks (60m2). Thehormon was used for implantation is HCG (pregnyl). The different dosage of hormon are 250Iu/Kg-1 ; 500 Iu/Kg-1 ; 750 Iu/Kg-1 . The result of this reaserch showed that egg development isMei-Juni (average of egg diameter is 1,4 mm) and Januari (average of egg diameter is 1,35 mm),Other month, the egg diameter was not develop or atresia. Treatment with 500 Iu/Kg-1 dossageshowed the best effect on oosit diameter was at 21 day and 63 day from first oosit diameter of0,9 mm to 1,4 mm.Keywords: Seasonal changes, gonadal maturation, implantation, kancera (Tor soro)